The biomechanical principles underpinning strength and conditioning - Goodwin, J. E.; Cleather, D. J. (Strength and conditioning for sports performance, 2016)
Biomechanics can be defined as the study of biological systems using tools from mechanics. The study ot biological systems encompasses a wide range of topics, which include the analysis of movement, the properties of biological tissues and the manufacture of devices and materials that complement biological performance. To this end, biomechanical principles underpin manv of the practical dav-to-dav problems faced by the strength and conditioning (S&C) coach. The purpose of this chapter is therefore to introduce some key biomechanical concepts and to highlight the practical relevance of biomechanical considerations to the daily practice of the S&C coach.